2015
DOI: 10.1248/bpb.b15-00260
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolin Acts as a Scavenger Receptor for Acetylated Low-Density Lipoprotein on Macrophages

Abstract: Although macrophage phagocytoses modified low-density lipoprotein (LDL), excessive accumulation of modified LDL induces macrophage foam cell formation, which is a feature of atherosclerotic plaque. Thus, the identification of scavenger receptor for modified LDL will provide better understanding of an atherosclerotic event. We recently showed that nucleolin expressed on macrophages acts as a scavenger receptor for various endogenous discarded products. Here, we investigated whether or not nucleolin is involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Moreover, we were able to pinpoint cell-surface nucleolin as one candidate protein required for the translocation of arginine-rich CPPs across membranes, since downregulation of nucleolin by siRNA (Figure B,C, Figure S6B) or blocking it with specific antibody on the GPMVs suppressed the accumulation of arginine-rich CPPs into the vesicles (Figure S6C). Nucleolin is an abundant protein that mostly resides in the nucleolus of mammalian cells; however, several reports have demonstrated that in some cells, mostly in cancerous ones, nucleolin is also targeted to the cell surface where it, among other functions, acts as a binding partner or a low-affinity coreceptor for several viruses ,, and lipoproteins. , In addition, the cellular uptake of a few synthetic compounds such as the guanosine-rich aptamer AS1411 and pentameric pseudopeptide HB-19 ,, is mediated by nucleolin that localizes on the cell surface. Indeed, nucleolin has several regions and modifications that might attract cationic CPPs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we were able to pinpoint cell-surface nucleolin as one candidate protein required for the translocation of arginine-rich CPPs across membranes, since downregulation of nucleolin by siRNA (Figure B,C, Figure S6B) or blocking it with specific antibody on the GPMVs suppressed the accumulation of arginine-rich CPPs into the vesicles (Figure S6C). Nucleolin is an abundant protein that mostly resides in the nucleolus of mammalian cells; however, several reports have demonstrated that in some cells, mostly in cancerous ones, nucleolin is also targeted to the cell surface where it, among other functions, acts as a binding partner or a low-affinity coreceptor for several viruses ,, and lipoproteins. , In addition, the cellular uptake of a few synthetic compounds such as the guanosine-rich aptamer AS1411 and pentameric pseudopeptide HB-19 ,, is mediated by nucleolin that localizes on the cell surface. Indeed, nucleolin has several regions and modifications that might attract cationic CPPs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Ncl was reported to act as a scavenger receptor for acetylated low-density lipoproteins on macrophages (Canton et al, 2013;Ezzat et al, 2015;Miki et al, 2015), and other receptor proteins may be involved in signalosomes. Thus, it is possible that Ncl interacts with 2OMePS, leading to reduced 2OMePS activity upon diminishing of a particular 2OMe-binding protein.…”
Section: Discussionmentioning
confidence: 99%
“…This can be done with various receptors, one of which is nucleolin. Nucleolin is used in microglia recognition of amyloid beta peptide 1–42 ( Ozawa et al, 2013 ), macrophage recognition of maleyated bovine serum albumin, and acetylated low-density lipoprotein ( Miki et al, 2015 ; Miki et al, 2015 ), to name a few. After recognition, there is the process of internalization through cytoskeleton rearrangement and, ultimately, degradation ( Uribe-Querol and Rosales, 2020 ).…”
Section: Binding and Uptake Of As1411mentioning
confidence: 99%